2020
DOI: 10.1001/jamaoncol.2019.4668
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Adherence to Anthracycline and Taxane-Based Chemotherapy, and Survival After Nonmetastatic Breast Cancer

Abstract: IMPORTANCE Although most chemotherapies are dosed on body surface area or weight, body composition (ie, the amount and distribution of muscle and adipose tissues) is thought to be associated with chemotherapy tolerance and adherence.OBJECTIVES To evaluate whether body composition is associated with relative dose intensity (RDI) on anthracycline and taxane-based chemotherapy or hematologic toxic effects and whether lower RDI mediates the association of adiposity with mortality. DESIGN, SETTING, AND PARTICIPANTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 33 publications
0
40
0
1
Order By: Relevance
“…[4][5][6][7] In this regard, overweight and obesity, weight gain or loss during treatments, as well as muscle and adipose tissue measurements have received increasing attention as potential prognostic factors as well as predictors of treatment-related toxicities. 8,9 There is a substantial body of evidence supporting the relationship between being overweight or obese with worse outcomes in patients with early-stage BC, especially in estrogen receptor (ER)-positive BC. 10 However, in the metastatic setting, little is known and most data comes from retrospective and institutional case series, with conflicting results reported so far.…”
mentioning
confidence: 99%
“…[4][5][6][7] In this regard, overweight and obesity, weight gain or loss during treatments, as well as muscle and adipose tissue measurements have received increasing attention as potential prognostic factors as well as predictors of treatment-related toxicities. 8,9 There is a substantial body of evidence supporting the relationship between being overweight or obese with worse outcomes in patients with early-stage BC, especially in estrogen receptor (ER)-positive BC. 10 However, in the metastatic setting, little is known and most data comes from retrospective and institutional case series, with conflicting results reported so far.…”
mentioning
confidence: 99%
“…One example is a study in a cohort of 151 early breast cancer patients treated with anthracycline and docetaxel or paclitaxel in which patients with a low SMI had significantly more adverse events [ 16 ]. Another study correlated visceral adipose tissue with safety parameters in 1395 patients with non-metastatic breast cancer treated with an anthracycline and docetaxel and/or paclitaxel and found that patients with larger visceral adiposity had a lower cumulative dose suggesting a lower tolerability for the treatment [ 11 ]. These observations can be explained by the influence of adipose tissue on the taxane pharmacokinetic profile, and pharmacokinetics was correlated with body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle mass (i.e., skeletal muscle index, SMI), adipose tissue, and skeletal muscle density (SMD) (i.e., a measure for skeletal muscle quality and intramuscular fat infiltration) could potentially serve as predictive covariates, as they are associated with altered volumes of distribution, metabolism, and clearance of cytotoxic drugs [ 10 ]. Previous studies demonstrated a wide variation in muscle mass and visceral adipose tissue (VAT) in patients with identical BSA and/or body mass index (BMI), producing a heterogeneity in chemotherapy tolerance and treatment-related toxicity such as neutropenia [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Cancer Institute definitions, "a person is considered to be a survivor from the time of diagnosis until the end of life" (2). Even in the era of immunotherapy and personalized medicine, chemotherapy is expected to continue to be a cornerstone in the adjuvant and neoadjuvant treatment settings, yet without treatment or prevention the debilitating side effects of chemotherapy remain (3). Up to 40% of all breast cancer survivors have lingering cognition-related complaints, sometimes known as "chemobrain" or "chemofog, " but more correctly designated chemotherapy-induced cognitive impairment (CICI).…”
Section: Introductionmentioning
confidence: 99%